A study on the reliability and validity of the Turkish version of the MOOLS-CA2 in people with cancer - (:unkn) unknown (My University, 2002)
0

The aim of this study was to examine reliability and validity of the MQOLS-CA2 (Multidimensional Quality of Life Scale-Cancer) in people with cancer. Study sample was 72 people with cancer. Validity was established with content validity, construct validity and criterion validity. Content validity was made using literature review, expert review and acceptability rate. Factor analysis was used for construct validity. Comparing global score of the MQOLS-CA2 with the Medical Outcomes Study -MOS- 36 Item Short Form Health Survey (SF-36) made criterion validity. Reliability was assessed using the internal consistency and test-retest methods. MQOLS-CA2 showed good content validity. The acceptability rate was excellent (96%). Factor analysis confirmed the presence of 5 factors in the MQOLS-CA2. A strong correlation of the MQOLS-CA2 score with the SF-36 was coherent (r: 0.78, P<0.001). The results of the test-retest method of the MQOLS-CA-2 showed the stability of 5 subscales in the MQOLS-CA2. Reliability coefficient of the subscales found through test-retest ranged between 0.56 and 0.91. The Cronbach alpha was calculated as 0.76. Obtained findings suggest that the Turkish version of the MQOLS-CA2 is a valid and reliable tool that could be employed in quality of life research on people with cancer.
Keywords: Onkoloji